Dynamic drug combination methods for suppressing bacterial antibiotics resistance adaptation - Bhone, Myint Kyaw (2014)
Staphylococcus aureus (S. aureus) is a common pathogen that can cause high mortality and morbidity. Every year, many people die from S. aureus related infections. Methicillin resistant S. aureus (MRSA) strain is typically responsible for severe and complicated infections in human beings. For this reason it is also considered as one of the “Superbug”. It is resistant to many drugs and the glycopeptide vancomycin is the only available antibiotic that is active against MRSA infections. However, recent reports indicate that vancomycin intermediate-resistant MRSA strains are emerging worldwide. Therefore, there is a concern that MRSA would gradually become fully-resistant to vancomycin in the near future and newer treatment strategies or compounds that can effectively cure S. aureus related infections should be well underway before our last antibiotic runs out. Plants have been naturally used since the ancient times as medicine and still many plant compounds can be found in the treatment of major ailments such as malaria and cancer. Due to multi-drug resistance problems in clinical settings and the need for newer compounds, there is great interest in phytochemical research because of their hypothesized and proven antimicrobial activities. Combinations of synergistic phytochemicals and antibiotics are assumed to be a new option to solve the drug resistance problem. Their combination can increase the efficacy and the killing rate and the chance of resistance development can be delayed. In this study, the effects of using conventional antibiotics in combination with phytochemicals were studied by using checker board methods and time-kill assays using 12 S. aureus strains. Studies suggested that tannic acid was synergistic with fusidic acid, minocycline, cefotaxime and rifampicin and additive with ofloxacin and vancomycin. Quercetin showed synergism with minocycline, fusidic acid and rifampicin. In a particular treatment option, the stability of the compounds (drugs or phytochemicals) is important as it selects resistance development in bacteria. The stability and the effectiveness of conventional antibiotics or phytochemicals were studied by inducing single-step adaptive resistant development in MRSA. The duration it took to get phenotypic mutant strains for a particular drug/phytochemical concentration was compared individually or in combination. It was found that conventional antibiotics under study were less stable than phytochemicals and combination of synergistic phytochemicals together with antibiotics could delay resistance formation in MRSA. The effectiveness of using fixed sub-Minimal Inhibitor Concentration (MIC) of phytochemicals in combination with synergistic step-wise increasing concentration of antibiotics were observed in this study. It was found that giving sub-MIC concentrations of tannic acid, quercetin and gallic acid ethyl ester together with fusidic or rifampicin could overcome or delay the occurrence of adaptive resistance in MRSA strains. Combination therapies using two or more synergistic antibiotics have been used before and their effectiveness in resistance prevention is still questionable because of the stability and the dosing pattern of the compounds used. In this study, with the consideration of the effectiveness of phytochemicals in combination with synergistic antibiotics in resistance prevention or delaying effects on partner synergistic antibiotic, a new noble dynamic drugs dosing combination hypothesis was introduced and tested with 4 MRSA strains for a duration of 10 days and 30 days to understand short-term and long-term effects. Giving more than 20% (0.2 MIC) of tannic acid or quercetin together with synergistic fusidic acid was found to prevent adaptive or genetic mutations in MRSA strains. Phytochemicals are assumed to have multi-targeted actions. Many authors proposed possible mechanisms of action of phytochemicals and much research is done on individual proposed mechanisms. Possible mechanisms of action of synergistic phytochemicals under study were investigated by using the Ethidium Bromide Accumulation Assay. Tannic acid, quercetin and gallic acid ethyl ester exhibited efflux pump inhibiting activities against four MRSA strains. The effects of phytochemicals on MRSA mutant strains revealed that phytochemicals under study have the ability to lower severe mutant strains into less severe mutant strains by bringing down the MICs. This work opens up the research into the novel strategies but using currently available drugs and synergistic phytochemicals instead of depending on new drugs. This is particularly important because developing new drugs for the prevention of resistance adaptation of multi-drug resistant bacteria like MRSA is extremely time consuming, expensive and comes with a high failure rate.